2001
DOI: 10.1001/archpedi.155.9.1043
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a School-Based Tobacco-Use Prevention Program

Abstract: The TNT is highly cost-effective compared with other widely accepted prevention interventions. School-based prevention programs of this type warrant careful consideration by policy makers and program planners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 20 publications
1
68
0
2
Order By: Relevance
“…In order to achieve greater effectiveness, it is widely recognized that a smoking prevention programme should contain the following components (Raczynski and Di Clemente 1997): sustained treatment, characterized by booster sessions over several years (such as considering the intervention as a dose of vaccine to be administered each year for a certain period); reinforcement of the treatment within the community, involving parents and the mass media; and programming smoking prevention activities within a more comprehensive school health promotion programme. Lastly, Wang et al (2001) have demonstrated that a school-based tobacco-use prevention programme, the Project Toward No Tobacco Use (TNT) designed to prevent tobacco use among high school students, is highly cost-effective, if compared with other prevention interventions. Such results have to be taken into serious consideration by policy makers and programme planners.…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve greater effectiveness, it is widely recognized that a smoking prevention programme should contain the following components (Raczynski and Di Clemente 1997): sustained treatment, characterized by booster sessions over several years (such as considering the intervention as a dose of vaccine to be administered each year for a certain period); reinforcement of the treatment within the community, involving parents and the mass media; and programming smoking prevention activities within a more comprehensive school health promotion programme. Lastly, Wang et al (2001) have demonstrated that a school-based tobacco-use prevention programme, the Project Toward No Tobacco Use (TNT) designed to prevent tobacco use among high school students, is highly cost-effective, if compared with other prevention interventions. Such results have to be taken into serious consideration by policy makers and programme planners.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its relevance, CEA has been sparsely utilized in the public health literature, in general, and with behavioral interventions for youth, in particular (Wagner and Goldstein 2004). We are aware of only two studies that have assessed the costeffectiveness of tobacco-use prevention programs implemented in US schools (Tengs et al 2001;Wang et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effectiveness study of Wang et al (2001) evaluates the school-based prevention programme "Project Towards No Tobacco Use (TNT)" (Dent et al 1995) which was designed to prevent the tobacco consumption of students. The programme was only effective in the combination of social influence curricula (health consequences, informational social influence and a normative social influence) for preventing the continuous use of tobacco.…”
Section: Resultsmentioning
confidence: 99%
“…Tengs et al (2001) consider the analysed anti-tobacco education to be beneficial to health and cost-effective for most plausible scenarios. Interestingly, Wang et al (2001) evaluate the same school-based prevention programme as cost saving regarding the medical savings for smokingrelated diseases and even more cost-effective without medical savings in all scenarios. The cost-effectiveness of US $481 up to US $2,770 per life year saved (excluding medical care cost savings) is also comparable with the costeffectiveness of smoking cessation programmes for adults.…”
Section: Discussionmentioning
confidence: 99%